Commonwealth Broadcasting Association handbook 1987/88 (Secretariat of the Commonwealth Broadcasting Association LondonGB, 1987)
Records historical background of the Commonwealth Broadcasting Association, its membership, activities, training of staff and describes cooperation between members. Summarizes proceedings of General Conferences held between 1945 and 1986. Provides background information on each of the 56 member organizations of the Association including the services they offer, the local electricity supply, the local standard time, television system, and the number of TV and radio sets.
IDS